Max's restaurant workforce profile, human resource management and employee performance - Buaron, Krista Pauline; Capulan, Karen; Cerbas, Gay Pollen; Dalmacio, Mary Leann; Gicole, Sheina Marie; Muyco, Norijan (2018.)
This study examines the workforce profile, human resource management practices, and employee performance in Max's Restaurant. Specifically, it looks at the demographics and composition of Max's workforce, the recruitment, training, and motivation techniques practiced by the management, and the level of productivity and relations of the employees with customers, fellow employees, and supervisors. The study employed the descriptive research design, specifically observational method, survey, and interview schedule. The respondent of the study consisted of thirty employees of Max"s Restaurant, ten from the Diversion Road branch and twenty from the SM City Iloilo branch. An interview with the restaurants human resource manager was conducted for additional data. The findings of this study provide information and insights on the processes and procedures by Max's Restaurant human resource department in managing their employees and may be useful for organizations of the same nature and also for future researches.
Preliminary Research Paper (Mgt 199 - Management Research). -- Iloilo City : University of the Philippines Visayas - College of Management, December 2018.